'Une chaîne invisible’: contemporary artistes, feminist self-representation, and the work of Annie Ernaux - Williams, Harriet Grace (2020)
This dissertation studies the work of French author Annie Ernaux in comparison with that of three contemporary artistes – Louise Bourgeois, Annette Messager, and Yayoi Kusama – inspired by Ernaux’s own concept of ‘une chaîne invisible’. Following a consideration of the existing intertextual and intermedial scholarship on Ernaux’s work, I discuss feminism, autobiography, and women’s self-portraiture. I address the following questions: how do these women create self-representations? To what extent are such works feminist? How do they link to each other? Each chapter focuses on one artiste, comparing and contrasting their work to that of Ernaux, as well as referencing various aspects feminist art where relevant in order to locate these women in their socio-historic-artistic contexts. My choice of Ernaux works offers intimate pieces of her self-representation: Passion simple (1991), Journal du dehors (1993), La Vie extérieure (2000), L’Événement (2000), Se perdre (2001), and L’Usage de la photo (2005). This art-based reading highlights the ways in which Ernaux’s corpus interacts with feminist art history and visual culture. This is the first project that analyses Ernaux’s work in relation to multiple artistes and is only the beginning of the use of the ‘chaîne invisible’ as a framework. Through text and image analysis, I examine diverse themes such as sexuality, illness, and death, demonstrating that it is in fact appropriate to call Ernaux an artiste due to the richness of her links with these women. I not only illuminate the work of Ernaux, but also that of the artistes, and I ultimately imply that more consideration should be given to such intermedial matters in future scholarship.